Burden of Non-communicable Diseases in a Western Mountainous Region of Nepal: a Hospital Based Study - Samal, Anup Mangal (Journal of Karnali Academy of Health Sciences, 2020)
Background: Non-communicable diseases (NCDs) are medical conditions or diseases that are nontransmissible from one person to another. NCDs have become the leading cause of morbidity and mortality worldwide. The objective of this study is to determine the burden of NCDs in a tertiary level general hospital in a mountainous region of Nepal. Methodology: A hospital based retrospective study was conducted in Karnali Academy of Health Sciences (KAHS). Data was collected from admission registers that contained information of patients (15 or more years of age) admitted to medicine ward during July 2019- October 2020. Statistical analysis was done using SPSS 22. Results were expressed in frequency and percentage. Results: Out of 762 total cases admitted, prevalence of NCDs was more than the half (55.6%). 49% of the patients were older people with age more than sixty years and most of the patients were female (61%). Brahmin/ Chhetri comprised the most common ethnic group (60%). COPD was the most common NCD (56%) followed by CVD and ARD (18% and 5% respectively). Most of the patients of COPD (63.75%) were more than sixty years of age two-third cases of COPD (65%) were female. Conclusions: NCDs contribute to a notable burden of disease in the rural mountainous region of the Karnali. Chronic respiratory disease and diseases related to cardiovascular origin constitute the top causes of morbidity. Stakeholders of health care should come up with concrete strategies to fight this growing health concern.